Increased platelet aggregation and serum thromboxane levels in aspirin-treated patients with prior myocardial infarction - Larsen, Sanne Bøjet; Neergaard-Petersen, Søs; Grove, Erik Lerkevang; Kristensen, Steen Dalby; Hvas, Anne-Mette (Thrombosis and Haemostasis, 2012)
The antiplatelet effect of aspirin displays considerable inter-individual variability. We investigated the antiplatelet effect of aspirin in patients with coronary artery disease on aspirin mono-therapy with and without prior myocardial infarction (MI). Further, we investigated whether the effect of aspirin differed between patients with and without aspirin use at the time of MI onset. We performed a study on 231 patients, including 171 with prior MI. Among patients with only one prior MI (116 patients), 59 patients were on aspirin at the time of MI onset. All patients received 75 mg aspirin as mono-therapy. Platelet aggregation was assessed by multiple electrode aggregometry (Multiplate®) and Verify -Now®, and platelet activation was evaluated by soluble P-selectin. Furthermore, we measured serum thromboxane B2. MI patients had higher median platelet aggregation levels than patients without prior MI when evaluated by Multiplate® (parachidonic acid<0.0001, pcollagen=0.20). This was not supported by VerifyNow®. Furthermore, MI patients had higher median serum thromboxane B2 levels than patients without prior MI (p=0.01). Patients on aspirin before MI onset had significantly higher median aggregation levels compared with MI patients not on aspirin when evaluated by Multiplate® (pcollagen=0.02) and VerifyNow® (p<0.0001). In conclusion, patients with prior MI had higher platelet aggregation levels than patients without prior MI when evaluated by Multiplate®, despite same aspirin dose and optimal compliance. Serum thromboxane B2 levels were higher in MI patients than in patients without prior MI. Finally, patients on aspirin before MI onset had higher aggregation levels compared with patients not on aspirin.
Keywords: Aspirin resistance; ischaemic heart disease; thrombosis; antiplatelet agents